Effect of Surface Texturing on Friction and Lubrication of Ti6Al4V Biomaterials for Joint Implants - Ranuša, Matúš; Odehnal, Lukáš; Kučera, Ondřej; Nečas, David; Hartl, Martin; Křupka, Ivan; Vrbka, Martin (Springer Nature, 2025)
The number of endoprosthetic implants for both large and small joints is increasing at a steady rate, thereby creating a growing demand for durable products that closely replicate the functionality of human joints. Notwithstanding the aforementioned advancements, challenges pertaining to implant fixation and tribological surfaces persist. The advent of progressive technologies, such as three-dimensional printing, offers a promising avenue for addressing these challenges in implant design and surface engineering. The Ti6Al4V and CoCrMo alloys, renowned for their biocompatibility and osseointegration properties, represent promising printable materials, although they are susceptible to wear on articulating surfaces. In order to mitigate the effects of abrasion, it is essential to implement surface treatments to facilitate the formation of a robust lubricating film. This research investigates the potential of texturing and electrochemical polishing to enhance protein aggregation in the contact area. The study employs a reciprocating simulator and colorimetric interferometry to observe the contact area and measure the coefficient of friction (CoF) of modified surfaces. The findings demonstrate that textured surfaces and the combination of electrochemical polishing result in an increase in the thickness of the protein lubrication film, which may potentially reduce wear. These outcomes suggest the potential for the utilization of Ti6Al4V alloy implants with fewer elements manufactured by additive technology.

The number of endoprosthetic implants for both large and small joints is increasing at a steady rate, thereby creating a growing demand for durable products that closely replicate the functionality of human joints. Notwithstanding the aforementioned advancements, challenges pertaining to implant fixation and tribological surfaces persist. The advent of progressive technologies, such as three-dimensional printing, offers a promising avenue for addressing these challenges in implant design and surface engineering. The Ti6Al4V and CoCrMo alloys, renowned for their biocompatibility and osseointegration properties, represent promising printable materials, although they are susceptible to wear on articulating surfaces. In order to mitigate the effects of abrasion, it is essential to implement surface treatments to facilitate the formation of a robust lubricating film. This research investigates the potential of texturing and electrochemical polishing to enhance protein aggregation in the contact area. The study employs a reciprocating simulator and colorimetric interferometry to observe the contact area and measure the coefficient of friction (CoF) of modified surfaces. The findings demonstrate that textured surfaces and the combination of electrochemical polishing result in an increase in the thickness of the protein lubrication film, which may potentially reduce wear. These outcomes suggest the potential for the utilization of Ti6Al4V alloy implants with fewer elements manufactured by additive technology.
Effect of Surface Texturing on Friction and Lubrication of Ti6Al4V Biomaterials for Joint Implants
Keywords: Ti6Al4V; Micro-texture; Implant; Optical interferometry; Friction; Film thickness; Ti6Al4V; Micro-texture; Implant; Optical interferometry; Friction; Film thickness